Dynamic assessment of the long-span cable-stayed bridge and traffic system subjected to multiple hazards - Zhou, Yufen, author; Chen, Suren, advisor; Ellingwood, Bruce R., committee member; Mahmoud, Hussam N., committee member; Sakurai, Hiroshi, committee member (Colorado State University. Libraries, 2016)
Critical infrastructure systems, such as long-span bridges, offer the underlying foundation for many aspects of modern society, such as national security, quality of life and economy. Although the total number of long-span bridges is relatively small compared to short-span and medium-span bridges, long-span bridges often serve as backbones for critical interstate transportation corridors and also evacuation routes. Any traffic disruption due to bridge damage, failure, retrofitting or even major traffic accidents following some hazards can become disastrous to local community and emergency response efforts, underscoring the importance of the continued integrity, functionality and resilience following hazardous conditions. Wind and traffic are the major service loads for long-span bridges. The extreme loads may include those caused by various natural or man-made hazards, such as earthquake, hazardous winds (hurricane, tornado), fire, blast, vehicle and barge collision etc. Compared to other hazards, hazardous wind and earthquake are particularly critical for long-span bridges, primarily due to their significant threats to the global structure performance and challenges of appropriately modeling the dynamic coupling effects between the bridge, traffic and hazards. In addition, there is another disastrous event: cable loss, which is very unique and critical for cable-supported bridges and could be caused by various natural and man-made hazards. There exist major challenges in the current state of the art on rationally predicting the long-span bridge performance subjected to multiple service and extreme loads. These challenges include realistic load characterization, methodological limitations and considerations of uncertainties. A suite of holistic analytical frameworks of long-span cable-stayed bridges subjected to various service and hazardous loads are developed, with which insightful numerical analyses of the bridge performance subjected to these loads are carried out in this dissertation. Firstly, two general dynamic assessment frameworks are developed based on the mode superposition and finite element methods respectively for a long-span cable-stayed bridge and traffic system subjected to multiple threats, such as stochastic traffic, wind and some hazardous loads. Although developed based on a long-span cable-stayed bridge, the frameworks can be readily applied to long-span suspension bridges as well as bridges with shorter spans. In both simulation platforms, the bridge model and all individual moving vehicles in the stochastic traffic flow are directly coupled under multiple excitations from bridge deck roughness and other external dynamic loads. Through the established simulation platforms, the global dynamic responses of the bridge and each individual vehicle subjected to various service and extreme loads can be rationally predicted in the time domain. Secondly, built on the proposed general simulation platforms, a novel dynamic safety assessment model and a vehicle ride comfort evaluation model for the bridge-traffic system are further developed. Thirdly, also extended from the proposed simulation platforms, both deterministic and reliability-based assessment frameworks for long-span cable-stayed bridges subjected to breakage of stay cables are established by considering more rational service load conditions as well as cable-breakage characterizations. Lastly, in addition to the in-house programs focusing on research purposes, a hybrid simulation strategy for the bridge under traffic and seismic excitations and a time-progressive simulation methodology for cable breakage events are also developed by taking advantage of the strength offered by commercial finite element software, e.g., SAP2000. These SAP2000-based strategies are expected to facilitate design engineers to more easily understand and conduct the related analyses in future engineering practices.
Keywords: dynamics; long-span bridge; wind; earthquake; cable breakage; traffic